Estudio de factibilidad ambiental para la implementación de algodón orgánico como materia prima sostenible en la industria textil colombiana. (2022)
This document presents, as its main objective, an environmental feasibility study for the implementation of organic cotton in the Colombian textile industry, which has been developed on a research scale in recent years in order to find an alternative to traditional cotton that is responsible to a greater extent with the conservation of the environment and the optimal use of natural resources. Initially, a global bibliographic search was carried out in order to identify current trends in the textile market, in terms of the life cycle of conventional cotton, including its transformation processes, where the advantages and disadvantages of its manufacture were identified. . Subsequently, renewable raw materials that replace conventional textile fiber were analyzed, thus finding that organic cotton is a viable and environmentally sustainable alternative that can be used in textile industries in Colombia, for which, through this investigation, it is proposed use this alternative as the main raw material for this type of industry, with the aim of mitigating the negative effects generated by conventional cotton, both for society and the environment.